Design of polarization-independent 1 × 2 optical power splitter based on silicon nitride slot waveguide structure - Fangxu Liu; Huanlin Lv; Hongyu Zhang; Shuo Liu; Yanfeng Liang; Haoyu Wang; Yang Cong; Xuanchen Li; Qingxiao Guo (Scientific Reports)
Abstract This paper introduces a novel design of a three-layer slot waveguide structure, serving as a polarization-independent optical power splitter based on Si/SiNx/Si materials. This design addresses the common challenges of structural complexity and high loss typically encountered in most polarization-independent optical power splitters. It achieves successful 1 × 2 power splitting for 1550 nm optical signals. The refractive index of the SiNx layer is tunable through the ion-assisted deposition method, which enables the alignment of output image points for both transverse electric (TE) and transverse magnetic (TM) modes, thereby achieving polarization-independent performance. The width of the Multimode Interference (MMI) region is reasonably selected to balance between device size and loss ensuring optimal performance. Additionally, an optimized tapered waveguide design has been incorporated to effectively reduce insertion loss. The device is simulated using the Frequency Domain Finite Difference (FDE) method and the Eigenmode Expansion (EME) method. Simulation results show that the coupling region of the device measures 4 μm×15.6 μm, with insertion losses for both TE and TM polarization modes below 0.034 dB at 1550 nm, and below 0.175 dB over a 100 nm bandwidth. This optical power splitter design holds significant potential for future integrated optical path applications.